Histogenesis of developing human fetal stomach - Munawara, Rafika; Kapoor, Kanchan; Sharma, Mahesh K.; Goel, Poonam; Chaudhary, Poonam (International Journal of Research in Medical Sciences, 2021)
Background: Human stomach is a highly specialised organ with distinct types of glands and microscopic features for its physiological activity. This study aimed to assess the chronological order in the development of different layers and the cyto-differentiation of various glandular cells in 50 fetuses from 12 weeks of gestation till term. Methods: Tissue was taken from cardiac, body and pylorus to investigate with light and confocal microscopy. Results: The gastric gland formation began as an indentation of the surface epithelium, gastric pit and simultaneous development of glandular buds in the mucosa. The pyloric glands preceded the development of cardiac and gastric glands showing retro cranial sequence of development. In contrast, the muscularis externa showed the classical craniocaudal model of development with oblique layer in the cardiac region by 14 weeks and body region by 16 weeks of gestation. The parietal cells were well developed by 12 weeks and the chief cells by 16 weeks with prominent secretory granules. In addition, the pyloric sphincter was a clearly defined anatomical sphincter developed by whorling of the inner circular layer at the pyloric end of the stomach evident from 12 weeks of gestation. Conclusions: The results showed that the significant cellular morphogenesis occurred between 12-20 weeks of gestation. This aggregated data will serve as a catalyst in the understanding intricacy of embryogenesis, pathogenesis tracing of congenital anomalies and invention of new drugs.